2013
DOI: 10.1016/j.reprotox.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol modulates expression of DNA methyltranferases and methyl CpG-/CpG domain-binding proteins in murine embryonic fibroblasts

Abstract: Fetal alcohol syndrome (FAS), presenting with a constellation of neuro-/psychological, craniofacial and cardiac abnormalities, occurs frequently in offspring of women who consume alcohol during pregnancy, with a prevalence of 1–3 per 1000 livebirths. The present study was designed to test the hypothesis that alcohol alters global DNA methylation, and modulates expression of the DNA methyltransferases (DNMTs) and various methyl CpG-binding proteins. Murine embryonic fibroblasts (MEFs), utilized as an in vitro e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 72 publications
4
24
0
Order By: Relevance
“…Similar degradation of DNA methyltransferases by ethanol exposure during the embryonic period was observed (Mukhopadhyay et al . ). However, this degradation is mediated through the ubiquitin–proteasome pathways (Mason et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar degradation of DNA methyltransferases by ethanol exposure during the embryonic period was observed (Mukhopadhyay et al . ). However, this degradation is mediated through the ubiquitin–proteasome pathways (Mason et al .…”
Section: Discussionmentioning
confidence: 97%
“…In an embryonic ethanol model, ethanol enhanced the expression of DNMT3A and 3B, but not DNMT1 (Mukhopadhyay et al . ) genes. A recent study reported that ethanol exposure significantly impaired DNA methylation (5‐mC staining) in both the dorsal and the ventral neural tube and that led to developmental delay (Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…The hsa-miR-214-3p mimic or miR-NC was introduced into HepG2 cells by transfection and the cells were incubated overnight. On the following morning, the transfected HepG2 cells were treated with 200 mM ethanol for 24 h prior to harvesting for RNA and protein analyses [26]. …”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms described include the degradation of DNA methyltransferases, and methyl binding proteins (MeCP2, Mbd2, and Mbd3) by proteasomal degradation, followed by DNA hypomethylation (Mukhopadhyay et al, 2013). The mechanisms described include the degradation of DNA methyltransferases, and methyl binding proteins (MeCP2, Mbd2, and Mbd3) by proteasomal degradation, followed by DNA hypomethylation (Mukhopadhyay et al, 2013).…”
Section: Alcoholmentioning
confidence: 99%